ANALISIS TINGKAT KESEHATAN KOPERASI SIMPAN PINJAM BERDASARKAN PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTRIAN KOPERASI DAN USAHA KECIL DAN MENENGAH REPUBLIK INDONESIA: (Studi kasus pada Koperasi Lembaga Keuangan Mikro Ngudi Lestari Desa Sanan, Girimarto, Wonogiri) - Setiawan, Edi; Fauzi, Yusran Abdul; Jaya, I Made Laut Mertha (PRIMA EKONOMIKA, 2021)
The purpuse of this research was to find out the level of healthy LKM Ngudi Lestari Girimarto from 2015-2019 that based on the regulation of the deputi field of supervision of the state ministry of cooperative and small and medium enterprise of republic indonesia No. 06/Per/Dep.06/IV/2016. The study was acase study. Subject of the research is the employee in LKM Ngudi Lestari Girimarto in 2015 until 2019. Object of the research is the level of healthy cooperative throught 7 aspect. Data was obtained through interview, observation, and questionare. The data analysis technique used in this research was a comparation technique based on the regulation of the deputi field of supervision of the state ministry of cooperative and small and medium enterprise of republic indonesia No. 06/Per/Dep.06/IV/2016 about the guidelines for the health assessment of cooperatives and units of savings and loans. Based on the analysis, it was found that in 2015 Ngudi Lestari Girimarto was categorized as â€œUnder Supervisionâ€, with total score 57,65. In 2016 was categirized â€œhealthy Enoughâ€, with total score 68,15. In 2017 was categorized â€œHealthy Enoughâ€, with total score 66,50. In 2018 was categorized â€œHealthy Enoughâ€, with the total score 67,75. In 2019 was categorized â€œHealthy Enoughâ€, with total score 70,25. Keywods: Level of saving loan, Perdep 2016.